PENGEMBANGAN MEDIA PEMBELAJARAN INFORMATIKA KELAS X DI SMK NEGERI 5 SELUMA PROVINSI BENGKULU - Ian Syaifullah Sikumbang; Haris Kurniawan; Adlia Alfriani (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
This study aims to develop interactive learning media based on Canva for the Informatics subject in Grade X at SMK Negeri 5 Seluma, Bengkulu Province. The development was carried out using the Research and Development (RD) method with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The media was designed to be engaging, interactive, and easy for students to understand, with content aligned to learning outcomes and featuring guidance, materials, instructional videos, evaluation games, and developer profiles. The validity of the media was tested by media experts, yielding an average score of 86.20% (very valid category), and by subject matter experts, with an average score of 81.25% (very valid category). Practicality tests showed that the media is highly practical to use, with scores of 85.42% from teachers and 84.51% from students. The results of this study indicate that interactive learning media based on Canva is suitable for use as a learning support tool for Computer Science, as it effectively enhances students' interest in learning and active engagement.